Honey-Mediated Synthesis Silver Nanoparticles and its Optical Characterization - Ismail, Nur Asyikin; Ameruddin, Amira Saryati (Enhanced Knowledge in Sciences and Technology, 2025)
This study explores a green method for synthesizing silver nanoparticles (AgNPs) using honey as a natural reducing and stabilizing agent, addressing the environmental concerns of conventional chemical methods. Honey's bioactive compounds enabled effective nanoparticle formation, with optimal results achieved under UV light, producing a surface plasmon resonance (SPR) peak at 420 nm and the highest absorbance of 1.70. Increasing honey concentration enhanced nanoparticle uniformity, with the smallest average size of 34.06 nm obtained at higher concentrations. FTIR analysis confirmed the role of hydroxyl and carbonyl groups in reduction and stabilization. This eco-friendly method offers a scalable alternative for AgNP production, demonstrating potential applications in medicine, catalysis, and environmental remediation.